Improving Walking Energy Efficiency in Transtibial Amputees Through the Integration of a Low-Power Actuator in an ESAR Foot - Alessandro Mazzarini; Ilaria Fagioli; Huseyin Eken; Chiara Livolsi; Tommaso Ciapetti; Alessandro Maselli; Michele Piazzini; Claudio Macchi; Angelo Davalli; Emanuele Gruppioni; Emilio Trigili; Simona Crea; et al. (IEEE, 2024)
Reducing energy consumption during walking is a critical goal for transtibial amputees. The study presents the evaluation of a semi-active prosthesis with five transtibial amputees. The prosthesis has a low-power actuator integrated in parallel into an energy-storing-and-releasing foot. The actuator is controlled to compress the foot during the stance phase, supplementing the natural compression due to the user’s dynamic interaction with the ground, particularly during the ankle dorsiflexion phase, and to release the energy stored in the foot during the push-off phase, to enhance propulsion. The control strategy is adaptive to the user’s gait patterns and speed. The clinical protocol to evaluate the system included treadmill and overground walking tasks. The results showed that walking with the semi-active prosthesis reduced the Physiological Cost Index of transtibial amputees by up to 16% compared to walking using the subjects’ proprietary prosthesis. No significant alterations were observed in the spatiotemporal gait parameters of the participants, indicating the module’s compatibility with users’ natural walking patterns. These findings highlight the potential of the mechatronic actuator in effectively reducing energy expenditure during walking for transtibial amputees. The proposed prosthesis may bring a positive impact on the quality of life, mobility, and functional performance of individuals with transtibial amputation.